MODEL-MODEL PEMBELAJARAN KONSTRUTIVISME - Nurhasnawati Nurhasnawati (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2011)
Contructivism is a learning model that emphasizes the recent activity of students in each interaction can be instructive to explore and discover his own knowledge. The flow of this constuctivism, in the study of science education is growing stream of theoretical cognitive psychology tha emphasizes the student to able to play an ative role in discovering new knowledge. Constructivism assumes that all learners ranging from child hood to college to have an idea or knowledge about the environment and events (symptoms) that occur in the surrounding environment, although this idea or knowledge often contructivism always retain this naïve idea or knowledge of the firm, because ideas or knowledge related to the idea or other knowledge in the form of sechemata (cognitive structures/knowledge). Learning constriktivism possible to provide better space for the involvement of students in the class room, to explore and dig deeper into the beauty and potential ability and behavior of a more open attitude.